Posey’s Selflessness In Her Altruism as Indicated In Mitch Albom’s for One More Day - Ramadhani, Riska Dewi; Pasopati, Rommel Utungga (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This paper explores the concept of selflessness in altruism, as demonstrated by Posey, the mother in Mitch Albom’s For One More Day. Through qualitative analysis, the study examines how Posey’s actions reflect altruistic behavior, focusing on her unwavering support and sacrifice for her son, Charley. The study investigates instances when Posey consistently puts her son’s needs above her own, even at the expense of her own personal interests. By analyzing specific moments in the novel, the study highlights Posey’s selflessness as an embodiment of altruistic love, demonstrating how her actions contribute to the emotional well-being and healing of her family. The analysis concludes that Posey’s selflessness is a profound representation of unconditional maternal love.